Rektrurisasi Efektifitas Penyaluran Dana Filantropi Islam Sebagai Upaya Percepatan Pertumbuhan Ekonomi Pasca Covid-19 - Fahmi, Aswin; Harahap, M Guffar; Tanjung, Aminullah Marlis; Radiansyah, M (Yayasan Rahmat Islamiyah, 2024)
The Covid 19 pandemic has produced quite a complex crisis, because Covid 19 has not only produced a health crisis but also a socio-economic crisis. This research aims to determine the impact of Islamic philanthropy distribution in overcoming the socio-economic crisis caused by the Covid 19 pandemic. This research will review in depth the Islamic philanthropy distribution programs carried out by zakat institutions in Medan City. This research also contains an evaluative element, to provide an evaluation to zakat institutions regarding the effectiveness and efficiency as well as the benefits received by mustahik from the implementation of Islamic philanthropy distribution programs in post-Covid 19. This research uses a qualitative research method. The author will explain in depth the findings that the author has obtained in the field, and then provide an interpretation, and arrange it systematically so that it is easy to understand. This research resulted in the conclusion that LAZISMU, IZI, and Dompet Duafa are considered effective in distributing the philanthropic funds that have been assessed, although there is some homework that must be completed by zakat institutions in distributing these philanthropic funds. This can be seen from two methods, namely, the ratio of the value of collection and distribution and the value of the benefits given to the distribution of Islamic philanthropy funds that have been carried out.